Child health studies following the 2023 Kahramanmaraş earthquakes: A bibliometric analysis of nursing research - Nurgül Özırmak; Yusuf Mirza Çalar; Yeliz Suna Dağ (Journal of Infant, Child and Adolescent Health, 2026)
Aim: Earthquakes are among the most destructive natural disasters. Children, whose cognitive and emotional development is ongoing, are particularly vulnerable to the adverse effects of such disasters. Pediatric nurses have important duties and responsibilities in the aftermath of disasters. This bibliometric study aims to comprehensively map scientific research in the field of pediatric nursing following the earthquakes that occurred on February 6, 2023. Method: Searches were conducted using the Web of Science and Scopus databases between February 2023 and June 2026. R Studio (Bibliometrix) software was used for data analysis. The primary types of analysis applied in the data analysis were collaboration analysis, word cloud, and co-word analysis. Results: A total of 35 research articles that met the inclusion criteria were included in the study. It was determined that the articles included in the study received a total of 1,279 citations, with an average of 3.17 citations per article. The thematic structure analysis revealed that core themes such as “earthquake, children, and post-traumatic stress disorder” were predominant in this field. However, it was determined that the terms “disaster nursing” and “nursing” were less prominent themes. Conclusion: These results indicate that research in this field focuses on the mental health issues and traumas experienced by children and adolescents following an earthquake. Furthermore, the fact that the terms “disaster nursing” and “nursing” emerged as less prominent themes highlights that disaster nursing is underrepresented in the literature and underscores the urgent need for scientific research in this area.